SHIFTING LEGAL LANDSCAPES: THE EVOLUTION AND FUTURE OF CUSTOMARY LAND RIGHTS RECOGNITION IN INDONESIA - Sukirno Sukirno; Muhammad Fahad Malik (Faculty of Law, Universitas Diponegoro, 2025)
This research explores the legal and political dynamics surrounding the recognition of customary land rights in Indonesia, from the Dutch colonial era to the post-Reformation period. The recognition of customary rights, a concept introduced by van Vollenhoven and later refined by Ter Haar, has evolved through various legal frameworks influenced by shifting political regimes. During the colonial period, Dutch policies acknowledged customary rights, particularly in indigenous areas like Riau and Jambi, though often in a limited and exploitative manner. Post-independence, however, the recognition of customary rights became more complex. The Old Order regime adopted a repressive stance, recognizing customary rights under strict conditions to avoid separatism, while the New Order further diminished these rights in favor of state land control, particularly for corporate interests. The Reform era introduced a somewhat more inclusive yet still restrictive approach to customary land rights, with legal frameworks acknowledging them in principle but often sidelining their practical application in favor of development agendas. This study analyzes these shifting policies using Nonet and Selznick’s framework of repressive, autonomous, and responsive law, concluding that Indonesia’s legal approach to customary rights has been predominantly repressive, with brief periods of responsiveness during certain regulatory changes. Looking forward, the research argues for a shift toward a responsive legal policy that actively involves indigenous communities in the legislative process and provides a clear, inclusive, and sustainable framework for recognizing and protecting customary land rights. Such a shift would be crucial in addressing the historical and ongoing marginalization of indigenous peoples in land-related issues, fostering a more equitable and participatory legal environment.